Hematological performances of African catfish (Clarias gariepinus) and media water qualities in culture system with bio-filtration pond - Sri Hastuti; Subandiyono Subandiyono (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
The aim of This study was to determine the effect of application biofiltration pond on water quality media and fish hematological performance consisting of erythrocytes, leukocytes, hemoglobin, hematocrit and platelets. Two treatments, namely water management systems with and without applied biofiltration pond to the catfish rearing system in the village of Beji, District East Ungaran. Dumbo Catfish Seed 8-10 cm in size were reared on the pond with a density 200 fish/m2. During the rearing of fish fed with pellets by the method of ad satiation, twice a day at noon and at night. Rearing the fish was done until size of consumption. At the end of the rearing carried out measurements of water quality conditions of temperature, pH, dissolved oxygen, carbon dioxide and ammonia, as well as hematological performance consisting of erythrocytes, leukocytes, hematocrit, hemoglobin, hematocrit and platelets. Data were analyzed descriptively. The results showed changes in leukocyte count from 107.57 thousand cells / ul to 92.3 thousand cells / ul. Platelets 42 000 cells / ul to 6000 cells / ul, while the erythrocytes and hematocrit values, each for 1.72 to 1.74 million cells / ul and 7.8 to 9.73 thousand cells / ul, water quality media were improvement, especially on the total ammonia content of 0.92 ppm to 0.14 ppm and dissolved oxygen is 0.08 ppm to 0.5 ppm. From the data can conclude that applied biofiltration pond on catfish farming systems can improve water quality media that support life and growth of fish. Keywords: African catfish, biofiltration pond , hematological performance, water quality managementhttp://ejournal.undip.ac.id/index.php/saintek/article/view/2067